Learning Prophets by Writing Prophecies: Modeling Amos to Critique Today's Problems - Litke, Andrew W. (Teaching theology and religion, 2025)
This article presents a group assignment that introduces undergraduate students to the biblical prophets: their original context, their attentiveness to social issues, and the rhetorical methods they utilize. In the assignment, students compose a prophecy set in the modern day that is modeled on the book of Amos. Due to the collaborative nature of the assignment and the way that it is structured, students must work together to discover points of commonality among themselves. After determining their prophet's persona and context, the students engage in social criticism as they compose their prophecy. In this article, the assignment and corresponding lectures are explained, and selections from student prophecies are presented.